#### Answer

5(x + (-2)) = 6x;
x = -10

#### Work Step by Step

"Five times the sum of a number and -1" translates to 5(x + (-1)).
"6 times the number" translates to 6x.
The expression is:
5(x + (-2)) = 6x
Solve for x:
5x - 10 = 6x
-10 = x

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

5(x + (-2)) = 6x;
x = -10

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.